Growth performance and nutrition value of Spirulina sp. under different photoperiod - Budiardi, Tatag; Priyo Utomo, Nur Bambang; Santosa, Asep (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
This study was conducted to analyze the production of freshwater Spirulina sp. cultured with photoperiod manipulation treatment. In this study, photoperiod manipulation treatment performed on cultured spirulina using fiber tanks (100 L). Spirulina was grown with different photoperiod (bright/T and dark/G) that are six hours per day (6T-18G), 12 hours per day (12T-12G), 18 hours per day (18T-6G), and 24 hours per day (24L-0G). The parameters were observed include dry biomass, population density (N), specific growth rate (SGR), doubling time (G), proximate analysis, and water quality. The results of this study showed that the optimum population density was achieved on day-3 days of cultured, and manipulation photoperiod showed no significant effect to the dry biomass harvest and population density, but significantly affect the specific growth rate and doubling time. Treatment of lighting 12, 18 and 24 hours per day to produce the maximum specific growth rate (0,345 to 0,366 per day) and a maximum doubling time (1,89 to 2,01 days) were not significantly different, whereas the old treatment six hours per day lighting showed the lowest maximum growth rate (0,323 per day) and highest doubling time (2,15 days). At treatment of lighting 12 hours per day, relatively higher protein content (39,73%) than others. In conclusion, the lighting 12 hours per day resulted in optimum production efficiency than other treatments.Keywords: Spirulina sp., photoperiod, density, biomass, growth, nutrition value. ABSTRAKPenelitian ini dilakukan untuk menganalisis produksi spirulina Spirulina sp. air tawar yang dikultur dengan manipulasi fotoperiode. Dalam penelitian ini, spirulina dikultur dalam wadah fiber 100 L dengan perlakuan fotoperiode (terang/T dan gelap/G) berbeda, yaitu enam jam per hari (6T-18G), 12 jam per hari (12T-12G), 18 jam per hari (18T-6G), dan 24 jam per hari (24T-0G). Parameter yang diamati meliputi biomassa kering, kepadatan populasi (N), laju pertumbuhan spesifik (SGR), waktu penggandaan (G), dan analisis proksimat sprirulina, serta kualitas air. Hasil penelitian menunjukkan bahwa kepadatan populasi optimum dicapai pada hari ke-3 umur kultur dan manipulasi fotoperiode tidak berpengaruh nyata terhadap hasil biomassa kering dan kepadatan populasi, namun secara nyata mempengaruhi laju pertumbuhan dan waktu penggandaan. Perlakuan pencahayaan 12, 18 dan 24 jam per hari menghasilkan laju pertumbuhan spesifik maksimum (0,345 sampai dengan 0,366 per hari) dan waktu penggandaan maksimum (1,89 sampai dengan 2,01 hari) yang tidak berbeda nyata, sedangkan perlakuan pencahayaan enam jam per hari menunjukkan laju pertumbuhan maksimum terendah (0.323 per hari) dan waktu penggandaan tertinggi (2,15 hari). Pada perlakuan pencahayaan 12 jam per hari, kandungan protein relatif lebih tinggi (39,73%) dari yang lain. Secara umum dapat disimpulkan bahwa pencahayaan 12 jam per hari menghasilkan efisiensi produksi yang lebih baik daripada perlakuan lainnya.Key word: Spirulina sp., fotoperiode, kepadatan, biomassa, pertumbuhan, kandungan nutrisi.